2001
DOI: 10.2527/2001.7992245x
|View full text |Cite
|
Sign up to set email alerts
|

Induction of sexual activity of male creole goats in subtropical northern Mexico using long days and melatonin.

Abstract: The aim of this study was to determine whether the sexual activity of local male Creole goats in subtropical Mexico can be induced during the non-breeding season by a long-day treatment followed by insertion of two melatonin implants. The experiment was carried out in the Laguna region in the State of Coahuila, Mexico (26 degrees N). Fourteen male goats were allocated to two balanced groups (n = 7 each) according to body and testicular weights. Males were kept together in two separate groups and fed lucerne ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
41
2
10

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 20 publications
6
41
2
10
Order By: Relevance
“…To our knowledge, no data exist about the medium-term effect of this treatment in goats. However, in bucks, the differences between groups are similar to those described by Delgadillo et al (2001) working with Creole bucks at subtropical latitudes, and by Guzmá n et al (2008) working at the same latitude and with a similar treatment to that used in this experiment. The reason for the difference in the onset of reproductive activity between groups treated with melatonin after the long-day treatment or those exposed to natural photoperiod was probably the exhaustion of the melatonin implant, which delayed perception of the natural long days.…”
Section: Discussionsupporting
confidence: 87%
“…To our knowledge, no data exist about the medium-term effect of this treatment in goats. However, in bucks, the differences between groups are similar to those described by Delgadillo et al (2001) working with Creole bucks at subtropical latitudes, and by Guzmá n et al (2008) working at the same latitude and with a similar treatment to that used in this experiment. The reason for the difference in the onset of reproductive activity between groups treated with melatonin after the long-day treatment or those exposed to natural photoperiod was probably the exhaustion of the melatonin implant, which delayed perception of the natural long days.…”
Section: Discussionsupporting
confidence: 87%
“…Recently, we found that treatment by long days followed by melatonin implants stimulates some sexual activity in Alpine bucks under temperate latitude (Delgadillo et al, unpublished results). However, the responses of Alpine males in terms of testosterone and sexual behavior were not as strong as those observed in the subtropics in this study or with local Mexican bucks (Flores et al, 2000;Delgadillo et al, 2001). The ovarian response of anestrous light-untreated Alpine does exposed to these Alpine long days and melatonintreated bucks was limited (50% of does ovulating; Delgadillo et al, unpublished results).…”
Section: Discussioncontrasting
confidence: 56%
“…Therefore, artificial photoperiod treatments could be used to modify the reproductive seasonality in males and females. Indeed, exposure of animals to 2 or 3 months of long -E-mail: joaldesa@yahoo.com days followed by either short days or a melatonin treatment, a hormone that mimics the effects of short days, stimulates their sexual activity during the non-breeding season (Donovan et al, 1994;Delgadillo et al, 2001;Chemineau et al, 2007). Another possibility to stimulate the sexual activity in anestrous females is the use of socio-sexual relationships.…”
Section: Introductionmentioning
confidence: 99%
“…On January 16, males of the experimental group received two subcutaneous ear melatonin implants and were then exposed to natural photoperiodic changes. This light-treatment during the non-breeding season stimulated LH and testosterone secretion, sexual behavior and sperm production from the end of February to the end of April (Delgadillo et al, 2001). Then, we tested whether these photoperiod-treated bucks could stimulate the sexual activity of anestrous goats.…”
Section: Control Of the Sexual Activity Of Male And Female Goatsmentioning
confidence: 95%